New evaluation index for the retainability of a swimmer's horizontal posture. - Yasunori Watanabe; Kohji Wakayoshi; Teruo Nomura (PLoS ONE)
This study aims to investigate the effect of changes in buoyancy when a swimmer respires in a horizontal posture. We attempted to evaluate the levelness of swimmers' streamline posture by simultaneously measuring the lung capacity and buoyancy under water. The buoyancy was measured based on the changes in the vertical loads of the upper and lower limbs on the subjects' streamline posture under water. The horizontal x-axis as lung ventilation and the vertical y-axis as buoyancy forms a linear equation y = ax + b. The relation between hand (upper-limb) buoyancy and lung ventilation is defined as y = a1x + b1 and that between foot (lower-limb) buoyancy and lung ventilation as y = a2x + b2. Horizontal levelness was calculated as a ratio by dividing a2 by a1 using the inclination (a) values from these formulas for an underwater streamline posture. We defined this ratio as the breathing-balance (BB) ratio. Although the performance levels in the present study did not show any difference in the absolute quantity of air that humans can inhale in a streamline posture, the BB ratio was higher in a statistically significant manner in junior swimmers competing at international levels compared with the other groups of subjects (P < 0.001). This statistical difference in horizontal levelness, despite the absence of a noticeable difference in the absolute quantity of inhaled air, may be attributable to the way in which each person inhales and exhales air. Top-level junior swimmers that exhibited a high BB ratio might have inhaled in a way that would counteract the sinking of the lower limbs, for example, through abdominal respiration. When exhaling, on the other hand, they might have let out air gradually to mitigate the acceleration force involved in submerging the lower limbs.